Influence of conditions of water production from air on the microbiocenosis of condensate - Kovalenko, Olena; Kormosh, Katerina; Velichko, Tetiana; Vasyliv, Oleg; Yemonakova, Oksana (Technology audit and production reserves, 2017)
The object of research is the microbiocenosis of water, produced from atmospheric air with the help of domestic conditioners of split systems. One of the most problematic places of study of this object is that the microbiocenosis of the aquatic environment is characterized by a considerable variety of microorganisms. Therefore, within the framework of this work, only microbiological indices determined by hygienic norms in force in Ukraine are determined. In the course of the study, standard methods and techniques are used for microbiological analysis of water samples, chemical analysis of atmospheric air samples, determination of atmospheric conditions, and laboratory equipment certified in Ukraine. As a result of the work done with the help of household air conditioners located at different distances from the coastal strip, industrial zone and transport highways, samples of atmospheric moisture condensates are obtained. The atmospheric conditions and the content of pollutants in the air in the places where water is produced from it, as well as the condensate flow under the given conditions, are determined. It is shown that the degree of atmospheric air pollution is most affected by the remoteness of air conditioners from industrial enterprises and transport highways. The influence of the height of placement of air conditioners above sea level and their remoteness of the coastal strip are insignificant. The indicators of epidemical safety of water from air have been experimentally determined, and the percentage relationships between families of bacteria and genera of mold fungi are established. The diversity of species composition of microorganisms present in water from air is shown and the influence of various external factors on the formation of such microbiocenosis is explained. It is proved that the water from the air, obtained with the help of domestic conditioners of split-systems, has a very low quality according to microbiological indices. Use such water for drinking or technical needs is possible only after its disinfection. And it is important to take into account that only correctly identified methods, reagents and technological scheme of water treatment will avoid the formation of harmful substances in the human body in water and contribute to improving the efficiency of the technology.